Forekomst, variasjon og kjønnsforskjeller av depressive symptomer blant barn og unge som deltar i ulike fritidsaktiviteter, en tverrsnittstudie - Juul, Else Marie Lysfjord; Hjemdal, Odin; Aune, Tore (Nordisk tidsskrift for helseforskning, 2020)
Prevalence, variation and gender differences of depressive symptoms among children and adolescents participating in various leisure activities, a cross-sectional studyDepressive symptoms among children and adolescents pose a significant health challenge, yet little is known about gender differences, incidence and variation of depressive symptoms. A population-based sample of children and adolescents aged 11-14, (N = 1748) was mapped for the occurrence of depressive symptoms across various leisure activities. The results show that those who participate in sports, either exclusively or in combination with cultural activities, report lower levels of depressive symptoms compared to those who only participate in cultural activities. The study confirms a considerable incidence of depressive symptoms among children and adolescents and provide new knowledge of variation in the incidence of depressive symptoms. The findings suggest that special attention should be paid to children and adolescents neither participate in sports, nor a range of leisure activities.